Bearing capacity charts of soft soil reinforced by deep mixing - Rashid, A.S.A. (Thomas Telford Services Ltd, 2017)
A series of preliminary design charts were developed to predict the bearing capacity of fully and partially penetrated deep mixing (DM) of soft soil. The charts were produced by a new numerical analysis tool based on discontinuity layout optimisation (DLO) in which a previously proposed homogenisation method was used to define the improvement area. To measure the applicability of implementation of the homogenisation method in the DLO, a series of validation processes was performed against several previous studies under uniform soil strength. A new empirical solution was developed from the DLO method using the homogenisation method for the bearing capacity of soft ground under uniform soil strength, improved by the fully penetrated DM method. Results produced by the DLO approach were compared with existing analytical solutions and better agreement was found from the present model. The charts consider variation in improvement area ratio, column length and strength, and foundation width for the fully and partially penetrated DM cases. The simulations were related to real field cases in which the strength characteristics of soft soil increase with depth. An example is given to demonstrate use of the charts. © 2017, Thomas Telford Services Ltd. All rights reserved.